1987
DOI: 10.1002/hep.1840070627
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and clinical outcome of hepatitis D virus (delta) infection in Jordan

Abstract: The epidemiology and clinical outcome of hepatitis D viral infection in HBsAg-positive acute hepatitis, chronic liver disease, primary hepatocellular carcinoma and the symptomless carrier state was studied in Jordan. The prevalence of hepatitis D viral infection was significantly higher in patients with chronic liver disease (18/79, 23%) and acute hepatitis (17/108, 16%) than in symptomless HBsAg carriers (2/136, 2%). The highest prevalence of hepatitis D viral infection was found in patients with primary hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 46 publications
0
30
1
Order By: Relevance
“…Two studies from Turkey show prevalence of anti-HDV in 18.8% to 23.0% of HBsAg positive HCC [37,76] . A Jordanian study reported the prevalence of anti-HDV in a small group of HBsAg positive HCC patients was 67%, but the sample size was very small [77] . The risk of HCC is increased in HDV infection compared to HBV monoinfection.…”
Section: Hepatitis D Virusmentioning
confidence: 99%
“…Two studies from Turkey show prevalence of anti-HDV in 18.8% to 23.0% of HBsAg positive HCC [37,76] . A Jordanian study reported the prevalence of anti-HDV in a small group of HBsAg positive HCC patients was 67%, but the sample size was very small [77] . The risk of HCC is increased in HDV infection compared to HBV monoinfection.…”
Section: Hepatitis D Virusmentioning
confidence: 99%
“…Epidemiologic data from neighbouring countries differ widely with regard to primary risk factors. It has been attributed to hepatitis C virus (HCV) infection in Saudi Arabia [8,9], hepatitis B virus/hepatitis D virus (HBV/HDV) infection in Jordan [10] and HBV and HCV in Turkey [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies will be discussed according to different geographic areas below. The prevalence rate of HDV infection in asymptomatic HBV carriers was reported as 2%, 31%, and 3.3% in Jordan, Kuwait, and Saudi Arabia, respectively [17][18][19]. In chronic liver diseases, it was reported as 23.5%, 23%, 2%, and 10% in Egypt, Jordan, Yemen, and Iran respectively [15,17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of HDV infection in asymptomatic HBV carriers was reported as 2%, 31%, and 3.3% in Jordan, Kuwait, and Saudi Arabia, respectively [17][18][19]. In chronic liver diseases, it was reported as 23.5%, 23%, 2%, and 10% in Egypt, Jordan, Yemen, and Iran respectively [15,17,[20][21][22]. The prevalence of HDV infection was low (0.5% to 13.3%) in Japan except in some islands of Okinawa, Russia except in Yakutia (18-20%), Korea, Indonesia (< 0.05%), Malaysia, Thailand (0.7%), Philippines and Vietnam (1.3%), and Lebanon (1.2%) [22].…”
Section: Introductionmentioning
confidence: 99%